Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan PT. Constructa Builders Duren Tiga Jakarta Selatan - Sabilla Nurul Fata; Fitri Sabina (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Abstrak. This study aims to determine the Influence of Work Motivation and Work Discipline on Employee Performance of PT. Constructa Builders South Jakarta both partially and simultaneously. The method used in this study is quantitative associative. The population and sample used in this study were all PT. Constructa Builders South Jakarta as many as 65 people. The sampling technique in this study used the Saturated Sample method (all members of the population can be research samples). The data analysis methods used by the author are Validity Test, Reliability Test, Classical Assumption Test, Regression Analysis, Product Moment Correlation Coefficient Analysis, Determination Coefficient Analysis and Hypothesis Testing. Partial hypothesis testing of the Work Motivation variable (X1) obtained a tcount value> ttable or (4.068> 1.999) where this is also proven by the significance of (0.000 <0.05). This means that there is a significant influence between the Work Environment and Employee Performance. Partial hypothesis test of work discipline variable (X2) obtained tcount value > ttable or (3.629 > 1.999) where this is also proven by the significance of (0.000 <0.05). This means that there is a significant influence between Work Discipline on Employee Performance. Simultaneous hypothesis test of work environment variable (X1) and work discipline (X2) obtained Fcount value > Ftable or (11.354 > 3.145) where this is also proven by the significance of (0.000 <0.05). This means that there is a significant influence simultaneously between Work Environment and Work Discipline on Employee Performance. The determination coefficient obtained R-Square value of 27% while the remaining 73% is influenced by other factors not examined in this study. Keywords: Work Motivation, Work Discipline, Employee Performance.